Penggunaan bahasa media luar ruangan di Surakarta dan relevansinya pada pembelajaran bahasa Indonesia teks iklan - Mukti, Bayu; Sulistyono, Yunus (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to (1) identify types of Indonesian speech errors in outdoor media writing in the city of Surakarta, (2) describe forms of correction for these speech errors, and (3) describe the relevance of speech errors in outdoor media writing from a perspective teaching Indonesian, especially those related to advertising texts. This research is qualitative descriptive research. The data for this research are outdoor media texts spread across various locations in the city of Surakarta. Recording techniques are used to record forms of language errors. Documentation techniques are used to document or record images in the form of external media. Data analysis with collected data, reducing data, analyzing data, and concluding data. The research results obtained 20 error data consisting of 3 capital letters, 2 punctuation marks, 13 written words and 2 abbreviated words. The error has been corrected as per Enhanced Spelling (EYD). This language error analysis has a significant relationship with Indonesian language subjects, especially advertising text materials. The results can be used as contextual teaching materials that enable students to understand and correct speech errors in everyday life as well as improve their skills in writing effective and compliant advertising texts